2006
DOI: 10.1016/j.ejvs.2005.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Plaque Texture Analysis Can Predict the Incidence of Silent Brain Infarcts Among Patients Undergoing Carotid Endarterectomy

Abstract: ME is a potent predictor of "silent" ischemic brain lesions among patients with carotid stenosis. An analysis of plaque texture can predict the degree of ME during endarterectomy and is more precise than the standard GSM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 31 publications
0
35
0
Order By: Relevance
“…Madycki et al [14] reported that plaque texture analysis can predict microemboli which are potent predictors of silent ischemic brain lesions during CEA. The risk of microemboli steadily increases with a decrease in the echogenicity of the plaque [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Madycki et al [14] reported that plaque texture analysis can predict microemboli which are potent predictors of silent ischemic brain lesions during CEA. The risk of microemboli steadily increases with a decrease in the echogenicity of the plaque [14].…”
Section: Discussionmentioning
confidence: 99%
“…The risk of microemboli steadily increases with a decrease in the echogenicity of the plaque [14]. Valton et al [15] found that the presence of embolic signals in patients with carotid stenosis was associated with the appearance of plaque ulceration.…”
Section: Discussionmentioning
confidence: 99%
“…From the etiological point of view, SBI can be thromboembolic or nonthromboembolic. Thromboembolic SBI is a consequence of thromboembolism in silent zones of the brain parenchyma possibly of cardiogenic origin or it can be caused by artery emboli, which is the reason for the existence of unstable exulceric carotid plaque to be considered the most frequent cause of SBI in asymptomatic ECD 13,[16][17][18] . According to the Asymptomatic Carotid Stenosis and Risk of Stroke (ACSRS) study, most registered SBI in asymptomatic ECD, for stenosis from 60% to 79%, are registered in male patients and is around 41%.…”
Section: Discussionmentioning
confidence: 99%
“…In effect, patients who have recent symptoms (comprising nearly 30% of our overall study population) are more likely to have recurrence of emboli, particularly with catheterization and stenting. For this reason, carotid plaque stability, ulceration, echolucency, and/or calcification are also hypothesized to impact the risk of CAS-associated microembolization [26][27][28]. However, some series have not found any significant associations between carotid plaque characteristics and the incidence of microembolization [16,29].…”
Section: Discussionmentioning
confidence: 99%